2022
DOI: 10.1111/myc.13481
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of 23 antifungal drugs against 54 clinical and environmental Aspergillus oryzae isolates

Abstract: The treatment of invasive aspergillosis caused by cryptic species remains a challenge due to the lack of randomised clinical trials and investigation of the efficacy and safety of different therapeutic strategies. We aimed to evaluate the in vitro activity of 23 conventional and new antifungal drugs against 54 clinical and environmental Aspergillus oryzae isolates by using the Clinical and Laboratory Standards Institute (CLSI) standard M38‐A3. The lowest geometric mean MIC values were found for luliconazole an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Other groups also demonstrated that combinations containing tioconazole, a conventional antimycotic drug, with acitretin as an alternative drug, lead to the disappearance of CMB lesions in a patient with psoriasis and CBM after 1 month of treatment [21]. Possibly, this combination was effective due to the different action mechanisms of both drugs: acitretin inhibits excessive cell growth and keratinization [31], reduces thickening of skin plaques, and tioconazole is an antifungal agent that ultimately inhibits ergosterol production [32]. Thus, by inhibiting the excessive development of plaques in the skin, acitretin may facilitate the passage of tioconazole to the place where the etiological agents of CBM parasitize, leading to their death.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups also demonstrated that combinations containing tioconazole, a conventional antimycotic drug, with acitretin as an alternative drug, lead to the disappearance of CMB lesions in a patient with psoriasis and CBM after 1 month of treatment [21]. Possibly, this combination was effective due to the different action mechanisms of both drugs: acitretin inhibits excessive cell growth and keratinization [31], reduces thickening of skin plaques, and tioconazole is an antifungal agent that ultimately inhibits ergosterol production [32]. Thus, by inhibiting the excessive development of plaques in the skin, acitretin may facilitate the passage of tioconazole to the place where the etiological agents of CBM parasitize, leading to their death.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, conidiophore stipes are brownish, short and smooth‐walled, and conidia are rough‐walled and globose (Figure 3C). Subsequently, the isolate was sequenced using the β‐tubulin gene as described previously 12,13 . Obtained sequences were compared with GenBank (http://www.ncbi.nlm.nih.gov) and MYCOBANK database (http://www.mycobank.org/page/Pairwise_alignment), and isolate (accession number OP244415) was identified as A. quadrilineatus by showing 100% similarity with the type strains of that species (accession numbers OL625674 and AB248335), which had been initially isolated from environments.…”
Section: Case Presentationmentioning
confidence: 99%
“…Subsequently, the isolate was sequenced using the β-tubulin gene as described previously. 12,13 Obtained sequences were compared with GenBank (www.ncbi.nlm.nih.gov) and MYCOBANK database (www. sequence data of Aspergillus species, section Nidulantes using 1000 bootstrap replicates.…”
Section: Morphological and Molecular Identificationmentioning
confidence: 99%